Manajemen dakwah : sebuah pengantar / H. Awaludin Pimay ; editor Machfud Syaefudin dan Anugroho. - AWALUDIN PIMAY, H.; Machfud Syaefudin; Anugroho (Pustaka Ilmu Group, 2013)
viii, 110 hlm. : ilus. ; 20 cm